Spawning Induction System of Puntius javanicus using Common Carp as a Trigger - M. Zairin Junior; R.K. Sari; M. Raswin (Jurnal Akuakultur Indonesia)
This study was carried out to determine the effect of induction using common carp as a trigger on spawning of Puntius javanicus.  Mature male and female of Puntius javanicus were reared in outer of the hapa that contains mature male common carp, mature female common carp, or mature male and female common carp as a control.  Common carp broodstock was injected or not injected by ovaprim.  The result of study show that the use of male common carp injected or not injected by ovaprim could induced spawning of Puntius javanicus, without the release of sperm and eggs of common carp.   Fertilization rate of Puntius javanicus eggs was high, reached of 91.4%, by using ovaprim-injected male common carp as trigger.